2017
DOI: 10.1016/j.devcel.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

PWP1 Mediates Nutrient-Dependent Growth Control through Nucleolar Regulation of Ribosomal Gene Expression

Abstract: Ribosome biogenesis regulates animal growth and is controlled by nutrient-responsive mTOR signaling. How ribosome biogenesis is regulated during the developmental growth of animals and how nutrient-responsive signaling adjusts ribosome biogenesis in this setting have remained insufficiently understood. We uncover PWP1 as a chromatin-associated regulator of developmental growth with a conserved role in RNA polymerase I (Pol I)-mediated rRNA transcription. We further observed that PWP1 epigenetically maintains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 86 publications
3
45
0
Order By: Relevance
“…S2 " type="url"/> ) in combination with ChIP to analyze Histone 4 lysine 12 (H4K12) acetylation, which is associated with active transcription, as well as H3K9 dimethylation, a repression-associated modification. Similar to the earlier observations on the Pol I target loci ( Liu et al, 2017 ), knockdown of PWP1 reduced the level of H4K12 modification on 5S rDNA loci ( Fig. 4 A), while increasing the level of repressive H3K9 dimethylation ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…S2 " type="url"/> ) in combination with ChIP to analyze Histone 4 lysine 12 (H4K12) acetylation, which is associated with active transcription, as well as H3K9 dimethylation, a repression-associated modification. Similar to the earlier observations on the Pol I target loci ( Liu et al, 2017 ), knockdown of PWP1 reduced the level of H4K12 modification on 5S rDNA loci ( Fig. 4 A), while increasing the level of repressive H3K9 dimethylation ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Our previous study showed that PWP1 acts downstream of nutrient-responsive mTOR signaling in vivo in Drosophila and that PWP1 is essential for the induced expression of the Pol I-dependent rRNAs in response to protein-rich diet ( Liu et al, 2017 ). As the Pol III-dependent gene expression is also dependent on nutrition ( Marshall et al, 2012 ), we wanted to test if Drosophila PWP1 (dPWP1, encoded by the nclb gene) controls the expression of Pol III-dependent 5S rRNA in this setting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations